Effect of postharvest application of calcium chloride on brown rot and quality of red-flesh dragon fruit (Hylocereus polyrhizus) - Awang Y.B.; Abdul Ghani M.A.; Sijam K.; Mohamad R.B.; Hafiza Y. (2024)
Indexed by Scopus